2023
DOI: 10.3390/cells12050818
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Lead Exposure Induces Behavioral and Cardiovascular Alterations Associated with Neuroinflammation

Abstract: The nervous system is the primary target for lead exposure and the developing brain appears to be especially susceptible, namely the hippocampus. The mechanisms of lead neurotoxicity remain unclear, but microgliosis and astrogliosis are potential candidates, leading to an inflammatory cascade and interrupting the pathways involved in hippocampal functions. Moreover, these molecular changes can be impactful as they may contribute to the pathophysiology of behavioral deficits and cardiovascular complications obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 90 publications
0
9
1
Order By: Relevance
“…Hypertension has been extensively documented in the scientific literature as one of the main health effects of lead exposure [23,24,[79][80][81]. However, in this study, compared to our previous results, we do not observe a concomitant baroreceptor reflex impairment, regardless of the type of exposure or gender [21,32,48,62,[82][83][84]. This lack of effect strikes a great interest, as the baroreceptor reflex is one of the main mechanisms regulating blood pressure, controlled by the higher autonomic brain regions, namely PVN-NTS axis and has been greatly characterized as one of the main autonomic effects in the presence of lead [81,[85][86][87][88][89].…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Hypertension has been extensively documented in the scientific literature as one of the main health effects of lead exposure [23,24,[79][80][81]. However, in this study, compared to our previous results, we do not observe a concomitant baroreceptor reflex impairment, regardless of the type of exposure or gender [21,32,48,62,[82][83][84]. This lack of effect strikes a great interest, as the baroreceptor reflex is one of the main mechanisms regulating blood pressure, controlled by the higher autonomic brain regions, namely PVN-NTS axis and has been greatly characterized as one of the main autonomic effects in the presence of lead [81,[85][86][87][88][89].…”
Section: Discussioncontrasting
confidence: 93%
“…Lead exposure has far-reaching health consequences, affecting multiple body systems due to its accumulation in the soft tissues [2,[5][6][7][8][9]11,[15][16][17][18][19], primarily influencing the cardiovascular and neurological systems. Long-term lead exposure has been related to cardiovascular issues such as hypertension and an increased risk of heart disease [20][21][22][23][24]. Furthermore, the neurological repercussions are especially troubling, since lead exposure has been linked to cognitive deficits, developmental delays, and behavioural abnormalities, particularly in children [25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigating the Effects of Lead on Memory Impairment in Post-Traumatic Stress Disorder: The prevalence of industrial and vehicular pollution has led to the introduction of certain scarce substances, such as lead, into the body, which exert unfavorable effects on the physiological system and organs of the body ( Shvachiy et al, 2023 ). Lead has been found to have a detrimental effect on the central nervous system ( Antonio et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lead exposure is considered one of the causes of neurological disabilities in both children and adults [ 3 ]. The study by Liana Shvachiy et al aimed to understand the molecular changes involved in the temporal remodeling of physiological functions during intermittent lead exposure [ 4 ]. They demonstrated that lead exposure in animals caused the inflammatory activation of microglia and astrocytes in the hippocampus with concomitant local neuroinflammation, consistent with changes in the reflex regulation of cardiovascular and respiratory parameters.…”
mentioning
confidence: 99%